Psychological and Psychiatric Correlates of Herpes Labialis - Weissler, Kinneret; Zelevich, Orly; Kreitler, Shulamith (Advances in Social Sciences Research Journal, 2025)
Herpes labialis (HL) has been studied very little from a psychological point of view despite its interest as a relatively nonsevere affliction and a cognate disorder to herpes genitalis, that has been studied extensively. The purpose was to study the psychological correlates of HL in several domains so as to establish whether there is a psychological profile characteristic for HL. The subjects were 89 HL patients recruited from three outpatient clinics and 92 controls matched in demographic characteristics to the HL patients. The subjects were administered instruments assessing personality dimensions (the Eysenck Personality Inventory), emotional tendencies (the Profile of Mood States and the Schalling-Sifneos scale of alexithymia) and psychiatric features (the Brief Symptom Inventory by Derogatis). The results showed that HL patients differed from controls in scoring significantly lower on anxiety and psychoticism (each according to two instruments), obsessive-compulsive tendencies, interpersonal sensitivity (inferiority) and alexithymia and in scoring higher on defensiveness, and the emotions of anger, vigor and interest. A discriminant analysis with the psychiatric scales as predictors enabled correct identification of 73% (p < .001) of the subjects. The conclusions are that there is a psychological profile chracteristic of HL, that it differs from that identified for herpes genitalis and that it is characterised by better mental health features than in the controls.